Bifurcation on diffusive Holling–Tanner predator–prey model with stoichiometric density dependence - Surendar, Maruthai Selvaraj; Sambath, Muniyagounder; Balachandran, Krishnan (Nonlinear Analysis: Modelling and Control, 2020)
This paper studies a diffusive Holling–Tanner predator–prey system with stoichiometric density dependence. The local stability of positive equilibrium, the existence of Hopf bifurcation and stability of bifurcating periodic solutions have been obtained in the absence of diffusion. We also study the spatially homogeneous and nonhomogeneous periodic solutions through all parameters of the system, which are spatially homogeneous. In order to verify our theoretical results, some numerical simulations are carried out.
Keywords: stability analysis; stoichiometry; food quality; Hopf bifurcation; predator–prey model